TO THE QUESTION OF DIGITALIZATION OF UNIVERSITIES IN THE CONTEXT OF STRIVING FOR ACADEMIC EXCELLENCE - Skiba, M.A.; Turganbaeva, A.R; Skaburskiene, N.; Pavalkis, D. (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2025)
The article examines the possibilities of integrating digital technologies into university activities across its four missions: teaching, research, employer engagement, and community interaction. These missions are considered indirect parameters of academic excellence, which can be used to assess the effectiveness of university education. The article also analyzes processes supporting university activities, particularly management processes. An attempt is made to develop scientific, methodological, and conceptual foundations for implementing the academic excellence initiative in higher education. The article provides detailed descriptions of digital platforms and tools corresponding to each of the university's missions aimed at achieving academic excellence. In conclusion, it is noted that digital transformation significantly impacts the achievement of academic excellence through several key aspects: access to resources, personalized learning, interactive teaching methods and virtual reality, flexibility and accessibility, collaboration and networking, analytics and evaluation, innovative research, and future skills development. Thus, digital transformation in universities creates conditions for a higher level of academic excellence by ensuring quality education that meets modern requirements and challenges.